ChemInform Abstract: Controlled Synthesis of Pnicogen—Chalcogen Polycations in Ionic Liquids. Issue 18 (April 2016) - Groh, Matthias F.; Isaeva, Anna; Mueller, Ulrike; Gebauer, Paul; Knies, Maximilian; Ruck, Michael
Abstract: New pnicogen—chalcogen compounds are synthesized using ionic liquids and characterized by single crystal XRD and DFT electronic structure calculations.